A Study of Island Network Performance for Streaming Protocols - Ammar Hatem Mohammed; Mahamad, Abd Kadir; Saon, Sharifah (Evolution of Information, Communication and Computing System, 2022)
Nowadays, video surveillance is a cornerstone of security in the world. It provides real-time monitoring for the alarm of the environment, for people as face recognition, for the property as plate car numbers detection, and provides a recorded archive for investigation. With megapixel cameras becoming increasingly widespread, even the bandwidth exhaustion of corporate networks is becoming a real issue. In this paper, a study on the island network’s performance using a streaming protocol of HTTP and RTSP to broadcast the IP camera when streaming executed on H264 and H.265 encoder was conducted. The research is done on the real island network that has been built as a test bed for the project. A network emulator (NetEm) was also used to inject the packet loss and delay to the island network in order to emulate a real network. Then the results were analyzed by Wireshark packet analyzer. Based on the results gained, it was found that HTTP over TCP has less packets when compared to RTSP. In conclusion, Hypertext Transfer Protocol is a little superior and authoritative protocol to stream a video compared to the RTSP protocol.